Respuesta :
Answer:
[tex]f(x) = 3 x^{2} + 6x +1[/tex]
Step-by-step explanation:
Since they give us the coordinates of the minimum of the parabola (the parabola's vertex), we start by writing the function in vertex form:
[tex]f(x) = a (x-xvertex)^{2} + yvertex = a (x- -1)^2 + (-2) = a (x+1)^2 - 2[/tex]
Now we use the fact that the point (0,1) is on the graph of the parabola, which means that when x=0, the value of the function (y) must be equal to 1.
We apply this to the expression we found above:
[tex]f(0) = a (0+1)^2 -2 = 1[/tex]
which gives us: [tex]a (1) -2 =1[/tex] therefore, [tex]a = 3[/tex]
Now we write the function using the value of the constant a we just found:
[tex]f(x) = 3 (x+1)^2 -2[/tex]
and next we find the square of the binomial (x+1) to express the function in standard form:
[tex]f(x) = 3 (x^2 +2x+1) -2 = 3x^2 +6x +3 -2 = 3x^2 +6x +1[/tex]